2021
DOI: 10.3390/molecules26175242
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of 2-(Trifluoromethyl)phenothiazine Derivatives with Two Hydroxyl Groups in the Side Chain-DFT and QTAIM Computations

Abstract: Phenothiazines are known as synthetic antipsychotic drugs that exhibit a wide range of biological effects. Their properties result from the structure and variability of substituents in the heterocyclic system. It is known that different quantum chemical properties have a significant impact on drug behavior in the biological systems. Thus, due to the diversity in the chemical structure of phenothiazines as well as other drugs containing heterocyclic systems, quantum chemical calculations provide valuable method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…In the D-A molecules, the positive charges of S atoms rise together with a significant increase in the negative charges of N atoms. The conjugated D-A compounds' bigger N and S atomic charge differences may result in higher ground-state dipole moments (8.11 D for PTZIDM) than the parent PTZ molecule (2.46 D)(Poła et al , 2021). Therefore, it may be concluded that both the acceptor as well as the donor of the D-A molecule interact intramolecularly.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…In the D-A molecules, the positive charges of S atoms rise together with a significant increase in the negative charges of N atoms. The conjugated D-A compounds' bigger N and S atomic charge differences may result in higher ground-state dipole moments (8.11 D for PTZIDM) than the parent PTZ molecule (2.46 D)(Poła et al , 2021). Therefore, it may be concluded that both the acceptor as well as the donor of the D-A molecule interact intramolecularly.…”
Section: Discussion and Findingsmentioning
confidence: 99%